Adsorption of Chromium(VI) and Zinc(II) Ions on the Skin of Orange Peels (Citrus sinensis) - Ekpete, O. A.; Kpee, F.; Amadi, J. C.; Rotimi, R. B. (Journal of Nepal Chemical Society, 2010)
The removal of heavy metal ions Cr (VI) and Zn (II) from aqueous solution using the skin of orange peel (Citrus sinensis) as an adsorbent under different experimental conditions was investigated in this study. The concentrations of the metal ions adsorbed were determined by atomic absorption spectroscopic (AAS) method. The parameters investigated were temperature, contact time, adsorbent dosage, initial metal ions concentration and pH. It was observed that the white inner skin of orange removed more of Cr (VI) than Zn (II) metal ions in all the adsorption experiments. The optimum removal of the Cr (VI) and Zn (II) metal ions occurred at pH 3 and at temperature 30°C. Application of the Langmuir isotherm to the systems yielded maximum adsorption capacity of 8.068 (mg/g) and 1.078 (mg/g) for Cr (VI) and Zn (II) metal ions respectively. Keywords: Orange peel; Adsorption; Heavy metals; Langmuir DOI: 10.3126/jncs.v26i0.3628 Journal of Nepal Chemical Society Vol. 26, 2010 Page:31-39